A computer-based comparative quantitative analysis of surgical outcome of mandibular reconstructions with free fibula microvascular flaps. Issue 2 (April 2014) - Leiggener, Christoph S.; Krol, Zdzislaw; Gawelin, Petter; Buitrago-Téllez, Carlos H.; Zeilhofer, Hans-Florian; Hirsch, Jan-Michaél
Abstract: The free fibula osteoseptocutaneous flap is the standard for reconstruction of extensive mandibular defects. The procedure must be precise to achieve the required functional and aesthetic results. The aim of the present study was to calculate retrospectively the exact differences in surgical outcome based on preoperative and postoperative Computed Tomography data sets. Ten patients with unilateral reconstructions of the mandible with a fibula based on conventional planning were analyzed quantitatively, applying mirroring techniques with direct comparison of the theoretically optimum with the actual reconstruction. The results showed that there is a significant discrepancy between what is actually achieved and the theoretical optimum. The result of the present retrospective analysis shows that there is room for further improvement of the outcome in complex mandible reconstruction cases.